In Silico Prediction Analysis of Idiotope-Driven T–B Cell Collaboration in Multiple Sclerosis - Høglund, Rune A.; Lossius, Andreas; Johansen, Jorunn N.; Homan, Jane; Benth, Jūratė Šaltytė; Robins, Harlan; Bogen, Bjarne; Bremel, Robert D.; Holmøy, Trygve (Frontiers in Immunology, 2017)
Memory B cells acting as antigen-presenting cells are believed to be important in multiple sclerosis (MS), but the antigen they present remains unknown. We hypothesized that B cells may activate CD4+ T cells in the central nervous system of MS patients by presenting idiotopes from their own immunoglobulin variable regions on human leukocyte antigen (HLA) class II molecules. Here, we use bioinformatics prediction analysis of B cell immunoglobulin variable regions from 11 MS patients and 6 controls with other inflammatory neurological disorders (OIND), to assess whether the prerequisites for such idiotope-driven T-B cell collaboration are present. Our findings indicate that idiotopes from the complementarity determining region (CDR) 3 of MS-patients on average have high predicted affinities for disease associated HLA-DRB1*15:01 molecules, and are predicted to be endosomally processed by cathepsin S and L in positions that allows such HLA binding to occur. Additionally, CDR3 sequences from cerebrospinal fluid (CSF) B cells from MS patients contain on average more rare T cell exposed motifs that could potentially escape tolerance and stimulate CD4+ T cells than CSF B cells from OIND patients. Many of these features were associated with preferential use of the IGHV4 gene family by CSF B cells from MS patients. This is the first study to combine high-throughput sequencing of patient immune repertoires with large scale prediction analysis, and provides key indicators for future in vitro and in vivo analyses.